Climate Change Education in Polish and UK National Curriculum Frameworks - Agnieszka Kozłowska (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Introduction The presence and the content of climate education in national curriculum frameworks of Poland and UK gains growing attention of researchers all over the world. Climate education addresses challenges of climate crisis and is an important part of ecological transformation in advanced economies. Research Aim The aim of the study was to compare Polish core curriculum and The National Curriculum of UK, in terms of presence climate change education in curricula's content. Material and Methods Material of the study were 2 documents: Polish core curriculum and British the National Curriculum. The study was limited to Key Stage 1-3 in the National Curriculum and kindergarten and primary school in the core curriculum. Content analysis was conducted using a categorisation key, with a set of words characteristic for a climate change concept. Results Climate change is absent in studied curriculum standards. Only 3 out of 19 key words were present in Polish base curriculum, whereas in the National Curriculum - 5 of them. In both cases key words' presence emerged without direct reference to climate change. Conclusion Both studied documents are devoid of climate change education.  The National Curriculum seems to be better in meeting the challenge of climate crisis, but differences are minor.  The result may be caused by centralisation and politicization of the procedure of constructing both the studied documents, which may be an obstacle for introducing new aspects of knowledge and attitudes. Political context of the results needs further studies under the concept of null curriculum of Elliot Eisner.